Shaken, but not stirred’: Sixty years of defining social innovation - Edwards-Schachter, Mónica; L. Wallace, Matthew (2017)
This paper examines the evolution in the conceptualization of Social Innovation (SI) with a view to elucidating the multiplication of uses of the term over the last half century. We performed a comprehensive and systematic literature review extracting 252 definitions of SI through a search of 2,339 documents comprising academic papers, books and book chapters, together research and policy reports. To guide the inductive analysis of pluri-vocal discourses we assume innovation to be a learning-based process involving actors’ interactions and social practices. We apply mixed qualitative methodologies, combining content analysis based on an interpretivist ontology with cognitive mapping techniques. Our findings show that SI was introduced as an analytical concept by incipient academic communities and has spread in the last decades as a normative concept fuelled by development and innovation policies. SI is defined by a set of common core elements underpinning three different and interrelated discursive ‘areas’: processes of social change, sustainable development and the services sector. We point to some policy implications and a number of promising avenues for research towards the advancement of a broader socio-technical theory of innovation.